Clinical, biochemical and molecular characterization of prosaposin deficiency. Issue 3 (19th February 2016) - Motta, M.; Tatti, M.; Furlan, F.; Celato, A.; Di Fruscio, G.; Polo, G.; Manara, R.; Nigro, V.; Tartaglia, M.; Burlina, A.; Salvioli, R.
Abstract : Prosaposin (PSAP) deficiency is an ultra‐rare, fatal infantile lysosomal storage disorder (LSD) caused by variants in the PSAP gene, with seven subjects reported so far. Here, we provide the clinical, biochemical and molecular characterization of two additional PSAP deficiency cases. Lysoplex, a targeted resequencing approach was utilized to identify the variant in the first patient, while quantification of plasma lysosphingolipids (lysoSLs), assessed by liquid chromatography mass spectrometry (LC‐MS/MS) and brain magnetic resonance imaging (MRI), followed by Sanger sequencing allowed to attain diagnosis in the second case. Functional studies were carried out on patients' fibroblast lines to explore the functional impact of variants. The two patients were homozygous for two different truncating PSAP mutations (c.895G>T, p.Glu299*; c.834_835delGA, p.Glu278Aspfs*27). Both variants led to a complete lack of processed transcript. LC‐MS/MS and brain MRI analyses consistently provided a distinctive profile in the two children. Quantification of specific plasma lysoSLs revealed elevated levels of globotriaosylsphingosine (LysoGb3) and glucosylsphingosine (GlSph), and accumulation of autophagosomes, due to a decreased autophagic flux, was observed. This report documents the successful use of plasma lysoSLs profiling in the PSAP deficiency diagnosis, as a reliable and informative tool to obtain a preliminary information in infantile cases with complex traits displaying severe neurological signs and visceral involvement. Abstract :